Morphine and Codeine in Oral Fluid after Controlled Poppy Seed Administration - Concheiro, Marta (Drug Test Anal, 2014)
Opiates are an important drug class in drug testing programs. Ingestion of poppy seeds containing morphine and codeine can yield positive opiate tests and mislead result interpretation in forensic and clinical settings. Multiple publications evaluated urine opiate concentrations following poppy seed ingestion, but only 2 addressed oral fluid (OF) results; neither provided the ingested morphine and codeine dosage. We administered two 45g raw poppy seed doses, each containing 15.7mg morphine and 3.1mg codeine, 8h apart to 17 healthy adults. All OF specimens were screened by on-site OF immunoassay Draeger DrugTest 5000, and confirmed with OF collected with Oral-Eze® device and quantified by liquid chromatography tandem mass spectrometry (1μg/L morphine and codeine limits of quantification). Specimens (n=459) were collected before and up to 32h after the first dose. All specimens screened positive 0.5h after dosing and remained positive for 0.5-13h at Draeger 20μg/L morphine cutoff. Maximum OF morphine and codeine concentrations (C(max)) were 177 and 32.6μg/L, with times to C(max) (T(max)) of 0.5-1h and 0.5-2.5h post-dose, respectively. Windows of detection after the second dose extended at least 24h for morphine and to 18h for codeine. After both doses, the last morphine positive OF result was 1h with 40μg/L 2004 proposed US Substance Abuse and Mental Health Services Administration cutoff, and 0.5h with 95μg/L cutoff, recently recommended by the Driving Under the Influence of Drugs and Medicines project. Positive OF morphine results are possible 0.5-1h after ingestion of 15.7mg of morphine in raw poppy seeds, depending upon the cutoff employed.